LAYANAN INFORMASI OLEH GURU BK UNTUK MENGETAHUI PERSEPSI SISWA TENTANG PENGINFORMASIAN HASIL TES INTELIGENSI - Ummah, Khairul; Ilyas, Asmidir; Sukma, Dina (Universitas Negeri Padang, 2013)
BK teachers have a very big role in providing an understanding of the different characteristics of students, which includes intelligence. Therefore, researchers feel the need to conduct research on student's perceptions about information intelligence test results through information services by BK teacher in high school Adabiah Padang. This study aimed descriptive form to describe the perceptions of students about information intelligence test results through information services by BK teacher. The population of this study were all high school students of class XI Adabiah Padang. Data collection tool was a questionnaire that reveals student's perceptions about information intelligence test results through information services by BK teacher, then the collected data were analyzed by using percentages. The findings of the study revealed that student's perceptions about information intelligence test results through information services by BK teachers belong to the category quite well. Based on the findings of the study suggested, should be able to provide more intensive information on the results of intelligence test, especially to students who do not understand the benefits and follow-up of intelligence test results obtained.